Personal Branding Remaja di Era Digital - Ascharisa Mettasatya Afrilia (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
Branding is a common thing done in the world of marketing. Branding is done to distinguish one product with other products so that raises its distinctive characteristics. Along with the development of branding context, now branding has penetrated to many lines including in the development of one’s self. This is then known as personal branding. This study looks into the analysis of personal branding teenagers represented by Gita Savitri. Gita Savitri is a teenage figure who is loved for his thoughts in dealing with many things about teenage life. One of the objectives of this research is to embody the teenager’s perspective in defining her identity. This is necessary because self-existence is a fundamental thing that must exist in a person including teenagers. This research uses qualitative descriptive method supported by eight main concept personal branding Peter Montoya. The results show that personal branding Gita Savitri meets the eight major concepts and covers the three main elements of personal branding namely You, Promise and Relationship.